(untitled) (TEST Trento Student Law Review, 2025)
The intersection of competition law and sector regulations often leads to jurisdictional overlaps, blurring the line between antitrust and sector regulation. This article delves into the complex landscape of jurisdictional conflicts between the Competition Commission of India (CCI) and sector-specific regulators in India’s regulatory framework. The paper meticulously examines the problems arising from these jurisdictional ambiguities, including forum shopping, legal uncertainty, and over-enforcement, which collectively harm consumer interests and undermine the efficiency of market regulation. The paper traces the roots of these conflicts to multiple sources, including ambiguous legislative provisions, inconsistent judicial interpretations, and the inherent challenges in delineating the boundaries between competition law and sector-specific regulations. In response to these challenges, the article proposes a multi-faceted approach to resolution. It advocates for enhanced cooperation between the CCI and sector regulators through mechanisms such as mandatory consultations, memorandums of understanding, and the establishment of dedicated working groups. The paper concludes by emphasizing the need for a harmonized approach that leverages the strengths of both the CCI and sector regulators to create a more coherent and effective regulatory framework in India.